2011
DOI: 10.1136/ard.2011.200317
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab in combination with methotrexate in Japanese patients with active rheumatoid arthritis: results of the GO-FORTH study

Abstract: ObjectiveTo assess the efficacy and safety of golimumab + methotrexate (MTX) in Japanese patients with active rheumatoid arthritis (RA).Methods269 Japanese patients with active RA despite treatment with MTX were randomised (1:1:1) to placebo + MTX (Group 1), golimumab 50 mg + MTX (Group 2) or golimumab 100 mg + MTX (Group 3). Subcutaneous golimumab/placebo was injected every 4 weeks; stable doses of oral MTX (6–8 mg/week) were continued. Patients were allowed to enter early escape (Group 1 added golimumab 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 22 publications
7
60
1
3
Order By: Relevance
“…While the safety and effectiveness of GLM in the younger group reported here corroborate previous clinical trial data [18,19,31,32], the current study demonstrated, for the first time, that the safety and effectiveness of GLM in elderly (75 B years) Japanese patients with active RA are comparable to those in younger (75[years) patients. It should be noted that, in elderly patients, the frequency of concomitant MTX use, which has been proven to be effective for anti-TNF agents, is lower than that in younger patients albeit with higher baseline disease activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While the safety and effectiveness of GLM in the younger group reported here corroborate previous clinical trial data [18,19,31,32], the current study demonstrated, for the first time, that the safety and effectiveness of GLM in elderly (75 B years) Japanese patients with active RA are comparable to those in younger (75[years) patients. It should be noted that, in elderly patients, the frequency of concomitant MTX use, which has been proven to be effective for anti-TNF agents, is lower than that in younger patients albeit with higher baseline disease activity.…”
Section: Discussionsupporting
confidence: 90%
“…Recent clinical studies in Japan, GO-FORTH [18] and GO-MONO [19], have demonstrated efficacy and safety of GLM in patients with active RA. However, elderly patients aged 75 years or over were excluded in both GLM clinical trials despite the fact that patients aged 70 years or over account for 35.4% of the total number of patients enrolled in the post-marketing surveillance (PMS) of GLM [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a Japanese trial of tocilizumab (61), increases in the total Sharp score (TSS) and its components and the erosion and joint narrowing scores were significantly lower with tocilizumab monotherapy than in DMARD therapy, providing the first evidence that biologics are superior to DMARDs for inhibiting structural damage. Subsequent clinical trials and studies of other biologic agents with methotrexate revealed a striking inhibition of structural damage, indicating that joint damage in RA can be attenuated (61)(62)(63)(64)(65)(66)(67) (Fig. 3).…”
Section: Biological Agents Targeting Cytokinesmentioning
confidence: 98%
“…West et al [39] partially confirmed these results, although the patients with high aTNF-a levels in their study had lower response rates to ADA. CTZ and golimumab have been studied less but appear to maintain this relationship [72][73][74][75]. UC presents lower response rates than CD in anti-TNF therapy.…”
Section: Since the Accent I (A Crohn's Disease Clinical Trial Evaluatingmentioning
confidence: 99%